The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c7pp00236j
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ultraviolet B (UV-B) radiation in combination with different temperatures in the early life stage of zebrafish (Danio rerio)

Abstract: Ultraviolet B (UV-B) radiation is an environmental stressor with detrimental effects on many aquatic organisms including fish. In addition, UV-B exposure combined with other environmental factors could have even more negative effects. The purpose of this study was to investigate the effect of UV-B radiation exposure on zebrafish embryos/larvae in terms of survival, developmental toxicity and the mRNA levels of the genes related to oxidative stress and innate immune response at different temperatures (24 °C, 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 48 publications
3
24
1
Order By: Relevance
“…However, there is no information provided from the authors regarding embryonic survival ability during previous stages of development, before the hatching process started (Abozaid et al, 2011). A pronounced adverse effect of increased water temperature as a perturbation factor in the embryogenesis process leading to increased mortality before 24 hpf was also observed in the study of Aksakal and Ciltas (2018).…”
Section: Embryonic and Post-embryonic Survival Abilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no information provided from the authors regarding embryonic survival ability during previous stages of development, before the hatching process started (Abozaid et al, 2011). A pronounced adverse effect of increased water temperature as a perturbation factor in the embryogenesis process leading to increased mortality before 24 hpf was also observed in the study of Aksakal and Ciltas (2018).…”
Section: Embryonic and Post-embryonic Survival Abilitymentioning
confidence: 99%
“…Cooling exposure at 50% epiboly stage for 6 and 18 hr in zebrafish embryos also resulted in a considerably reduced embryonic survival ability (control: 67.50% vs. 18 hr: 39.80% and 6 hr: 18.75%) during hatching process (Paes & Nakaghi, 2017 TA B L E 2 (Continued) inability of the emerging larvae to break down the eggshell along with malformations such as pericardial and yolk-sac oedema, tail deformity and spinal curvature (Aksakal & Ciltas, 2018).…”
Section: Embryonic and Post-embryonic Survival Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are still actively investigating the effect of thermally mediated phenotypic traits on life‐history traits and fitness. Some studies have shown negative effects of thermal challenges (Cingi, Keinänen, & Vuorinen, ; Icoglu Aksakal & Ciltas, ). In birds specifically, lower incubation temperatures have been linked to lower hatching success (Nord & Nilsson, ) and survival (Berntsen & Bech, ; Nord & Nilsson, ; Ospina, Merrill, & Benson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown negative effects of thermal challenges (Cingi, Keinänen, & Vuorinen, 2010;Icoglu Aksakal & Ciltas, 2018). In birds specifically, lower incubation temperatures have been linked to lower hatching success (Nord & Nilsson, 2011) and survival (Berntsen & Bech, 2016;Nord & Nilsson, 2016;Ospina, Merrill, & Benson, 2018).…”
mentioning
confidence: 99%